Clinical Recommendations of Russian Gastroenterological Association and RENDO Endoscopic Society on Diagnosis and Treatment of Gastritis and Duodenitis - V. T. Ivashkin; I. V. Maev; T. L. Lapina; E. D. Fedorov; A. A. Sheptulin; A. S. Trukhmanov; A. V. Kononov; R. A. Abdulkhakov; O. P. Alexeeva; S. A. Alekseenko; D. N. Andreev; E. K. Baranskaya; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The clinical guidelines are intended to supplement specialty decision-making for improved aid quality in patients with gastritis and duodenitis though acknowledging the latest clinical evidence and principles of evidencebased medicine.Key points. Gastritis is an inflammatory disease of stomach mucosa, with a separate definition of acute and chronic gastritis. Chronic gastritis is a cohort of chronic diseases uniting a typical morphology of persistent inflammatory infiltration, impaired cellular renewal with emergent intestinal metaplasia, atrophy and epithelial dysplasia of gastric mucosa. Oesophagogastroduodenoscopy (OGDS) or high-resolution OGDS with magnified or non-magnified virtual chromoendoscopy, including targeted biopsy for atrophy and intestinal metaplasia grading and neoplasia detection, are recommended to verify gastritis and duodenitis, precancer states and/or gastric mucosal changes. All chronic gastritis patients positive for H. рylori should undergo eradication therapy as aetiological and subsidiary for gastric cancer prevention. Chronic gastritis patients with symptoms of dyspepsia (epigastric pain, burning and congestion, early satiety), also combined with functional dyspepsia, are recommended proton pump inhibitors, prokinetics, rebamipide and bismuth tripotassium dicitrate in symptomatic treatment. With focal restricted intestinal metaplasia, follow-up is not required in most cases, mainly when advanced atrophic gastritis is ruled out in high-quality endoscopy with biopsy. However, a familial history of gastric cancer, incomplete intestinal metaplasia and persistent H. pylori infection render endoscopy monitoring with chromoendoscopy and targeted biopsy desirable once in three years. Patients with advanced atrophic gastritis should have high-quality endoscopy every 3 years, and once in 1–2 years if complicated with a familial history of gastric cancer.Conclusion. The recommendations condense current knowledge on the aetiology and pathogenesis of gastritis and duodenitis, as well as laboratory and instrumental diagnostic techniques, main approaches to aetiological H. pylori eradication and treatment of dyspeptic states.